(3bhGfjf GdCMcGe GdTQYjI heSGFd GdaQhY GdabgjIs - (3eMeO Hf CMeO Hf eMeO Hf YHO Gddg, GHf LRj GdcdHj, CHh GdbGSe,J (B741 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pj GdLdGd GdPj YLRJ Yf EOQGcg s
(3BNQgG (B:s
(3ced HMeO Gddg hMSf Yhfg hJhajbg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B325 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B11s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B244s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 175) s
Keywords: (3Gdabg GdeGdcjs